Paediatric acute lymphoblastic leukaemia and caesarean section: A report from the United Kingdom Childhood Cancer Study (UKCCS). Issue 3 (29th April 2020) - Bonaventure, Audrey; Simpson, Jill; Ansell, Pat; Roman, Eve
Abstract: Background: Reports have suggested that children born by caesarean initiated before labour onset may be at increased risk of developing acute lymphoblastic leukaemia (ALL). However, with most data being derived from case‐control study interviews, information on the underpinning reasons for caesarean section is sparse, and evidence is conflicting. Objectives: Use clinical records compiled at the time of delivery to investigate the association between childhood ALL and caesarean delivery; examining timing in relation to labour onset, and reasons for the procedure. Methods: Data are from the UK Childhood Cancer Study, a population‐based case‐control study conducted in the 1990s, when caesarean section rates were relatively low, in England, Scotland, and Wales. Children with ALL were individually matched to two controls on sex, date of birth, and region of residence. Information on mode of delivery and complications was abstracted from obstetric records. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using logistic regression models adjusted for matching variables and relevant covariates. Results: Around 75% of the 1034 cases and 1914 controls were born through unassisted vaginal delivery. Caesarean delivery was as frequent in cases and controls (OR 1.07, 95% CI 0.84, 1.36). No association was observed between ALL and caesarean delivery either during or before labour, with adjusted ORs of 1.08 (95% CI 0.78, 1.48) and 1.09 (95% CI 0.78, 1.53), respectively. For B‐cell ALL, the ORs were 1.14 (95% CI 0.81, 1.59) for caesarean during labour and 1.21 (95% CI 0.85, 1.72) for prelabour. The underpinning reasons for caesarean delivery differed between cases and controls; with preeclampsia, although very rare, being more common amongst cases born by caesarean (OR 8.91, 95% CI 1.48, 53.42). Conclusions: Our obstetric record‐based study found no significant evidence that caesarean delivery increased the risk of childhood ALL, either overall or when carried out before labour.